Older patients' consultations in an apprenticeship model‐based general practice training program: A cross‐sectional study. (22nd November 2016) - Bonney, Andrew; Morgan, Simon; Tapley, Amanda; Henderson, Kim; Holliday, Elizabeth; Davey, Andrew; van Driel, Mieke; Spike, Neil; Regan, Cathy; Ball, Jean; Magin, Parker
Abstract : Objective: To investigate older patients' encounters with general practice registrars (GPRs) to inform training and clinical practice. Methods: Cross‐sectional analysis of data from GPR consultations across five regional training providers in Australia. Data were analysed using simple and multiple logistic regression models. Results: Our analysis included details of 118 831 consultations, 20 555 (17.6%, 95% CI 17.4–17.8) with patients aged ≥65 years. Older patient encounters had an increased likelihood of including chronic disease (OR 1.77, 95% CI 1.70, 1.86) and more problems (OR 1.24, 95% CI 1.20, 1.27). However, in‐consultation information or advice was less likely to be sought (OR 0.92, 95% CI 0.88, 0.97), and consultations were briefer (OR 0.99, 95% CI 0.99, 1.00). Conclusion: Our results suggest relatively limited GPR exposure to older patients coupled with less complex consultations than expected. Solutions will need to be carefully constructed not only to increase caseloads, but also to address training and supervision concerns.